The Influence of Internal and External Factors on Student Learning Motivation in Physical Education Learning for Class XI Senior High School - Sahidallah; Ali Muhaimin; Johan Wahyudi (Universitas Pendidikan Mandalika, 2026)
Learning motivation is one of the important psychological factors that determine student involvement in physical education learning. This motivation is not only influenced by the motivation that comes from within the students, but also by the support of the learning environment that shapes their experience during the learning process. This study aims to analyze the influence of internal factors and external factors on students' learning motivation in physical education learning, by emphasizing its empirical contribution to the learning context of physical education in secondary schools. The research uses a quantitative approach with a correlation-predictive design. The research sample amounted to 40 students in grade XI of SMA Negeri 1 Kuripan. The research instrument was in the form of questionnaires of internal factors, external factors, and learning motivation. Data were analyzed using prerequisite tests and multiple linear regression. The results of the study show that all data meet the assumptions of normality, linearity, and do not experience multicollinearity, so the regression model is feasible to explain the predictive relationship between variables. The results of multiple linear regression showed an R value of .813, R Square of .661, and Adjusted R Square of .643, which means that internal and external factors together explain 66.1% of the variation in student learning motivation. The simultaneous test yielded an F value of 36,076 with a significance of <,001. Partially, internal factors had a positive and significant effect on learning motivation with a coefficient of .413, beta .480, t = 3.698, and p < .001, while external factors also had a positive and significant effect with coefficients of .401, beta .408, t = 3.144, and p = .003. These findings suggest that internal factors are relatively stronger predictors than external factors. Thus, the research hypothesis is accepted. This study confirms that strengthening confidence, interests, learning needs, teacher support, facilities, and learning environment need to be integrated into physical education learning strategies to increase students' motivation to learn more effectively.